PEMBUATAN MEDIA PEMBELAJARAN FISIKA BERBASIS MULTIMEDIA INTERAKTIF UNTUK MTS BUSTANUL ULUM PAKISAJI MENGGUNAKAN ADOBE FLASH - FIGOR AGUSYANA QOIRIAWAN, FIGOR AGUSYANA QOIRIAWAN (Jurnal Fakultas Teknologi Informasi, 2012)
ABSTRACTQoiriawan, Figor Agusyana. 2013. Physics-Based Media Interactive Multimedia LearningTo Mts Bustanul Ulum Pakisaji Requires Adobe Flash. StudiesProgram, Faculty of Information Technology University ofMalang Kanjuruhan. Supervisor: Alex Endy Budianto, S. Kom,MM.Keywords: Media Learning Physics-Based Interactive Multimedia.Visual media in the physical sciences in particular IPA is very minimal in encounter.Most students get learning materials only the source of information from books or teachers,which resulting in low visualization of the students on the material which is learn. It causesbored to the students in studying science. Computers can be used as atool to make theabstract concept concrete becomes static and animated visualizations. Through animation itcan make more attractive concept that adds to the motivation in learning the science. By thepossibility of making computers as interactive multimedia programs.Therefore, in order to learn the process of science is not boring and more interesting.The reseacher interested in conducting this thesis under title of